Finance or Food? : The Role of Cultures, Values, and Ethics in Land Use Negotiations - Bjørkhaug, Hilde; McMichael, Philip; Muirhead, Bruce (University of Toronto Press, 2020)
Exploring the ways in which culture, systems of value, and ethics impact agriculture, this volume addresses contemporary land questions and conditions for agricultural land management. Throughout, the editors and contributors consider a range of issues, including pressure on farmland, international and global trade relations, moral and ethical questions, and implications for governance. The focus of Finance or Food? is land use in Australia, Canada, and Norway, chosen for their commonalities as well as their differences. With reference to these specific national contexts, the contributors explore political, ecological, and ethical debates concerning food production, alternative energy, and sustainability. The volume argues that recognition of food, finance, energy, and climate crises is driving investments and reframing the strategies of development agencies. At the same time, food producers, small farmers, and pastoralists facing eviction from their land are making their presence felt in this debate, not just locally, but in national policy arenas and international fora as well. This volume investigates the many ways in which this process is occurring and draws out the cultural implications of new developments in global land use. An important intervention into a timely debate, Finance or Food? will be essential reading for both academics and policymakers.